The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1044/2020_jslhr-20-00182
|View full text |Cite
|
Sign up to set email alerts
|

Code-Switching and Language Proficiency in Bilingual Children With and Without Developmental Language Disorder

Abstract: Purpose This study examined the frequency of code-switching by Spanish–English-speaking children as a function of language proficiency in each language and diagnosis (developmental language disorder [DLD] or typical language development [TLD]). Method Sixty-two Spanish–English-speaking children, 5–7 years of age, participated in this study (24 with DLD and 38 with TLD). Language samples were used to determine the level of language proficiency in each la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…The result indicates that both groups switched codes with the same frequency. This result is similar to that reached by Montanari et al (2019) and Kapantzoglou et al (2021), who found no remarkable relationships between the frequency of CS and language proficiency. Furthermore, the analysis reveals that the high-level language proficiency group used more intrasentential code-switches than the intermediate level of language proficiency group, who used more intersentential code-switching during their speech.…”
Section: Results Related To Research Questionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result indicates that both groups switched codes with the same frequency. This result is similar to that reached by Montanari et al (2019) and Kapantzoglou et al (2021), who found no remarkable relationships between the frequency of CS and language proficiency. Furthermore, the analysis reveals that the high-level language proficiency group used more intrasentential code-switches than the intermediate level of language proficiency group, who used more intersentential code-switching during their speech.…”
Section: Results Related To Research Questionsupporting
confidence: 91%
“…For instance, Reyes (2004) found a significant statistical difference in the frequency of CS between two groups of bilinguals due to their levels of language proficiency. On Arab World English Journal www.awej.org ISSN: 2229-9327 313 the other hand, Montanari et al (2019) and Kapantzoglou et al (2021) found no remarkable relationships between CS in Spanish-English bilinguals and language proficiency. The contrastive results across studies might be attributed to the different methodological approaches of each study.…”
Section: Bilingual Proficiency and Frequency Of Csmentioning
confidence: 88%
“…During the scheduled interviews, parents of JC-Englishspeaking children in the current study completed the FOCUS in English only but considered how their children dynamically used communication across both of their spoken languages. Important to note is that code-mixing (i.e., use of features of both languages in a single production) is ubiquitous in the Jamaican context (Wright , in-keeping with observations of language use in other multilingual children (Castilla-Earls et al, 2016;Kapantzoglou et al, 2021;Paradis et al, 2021), offering ecological validity in support of our chosen approach. Based on availability at the time of data collection, the FOCUS or FOCUS-34 was used.…”
Section: Methodssupporting
confidence: 63%
“…However, when considering MLU as a metric for assessing multilingual children, researchers have identified MLU in words (i.e., MLUw; Gutierrez-Clellen et al, 2012) as a more responsive and accurate calculation. The MLUw calculation responds to differences across languages regarding morphological “rules, rate, and order” (Baron et al, 2018, p. 975) and addresses natural features of multilingualism, such as crosslinguistic influence (Baron et al, 2018; Kapantzoglou et al, 2021; Paradis et al, 2021). Because MLUw is unaffected by cross-linguistic influence and is more responsive to differences in morphemes (Baron et al, 2018), it is increasingly recommended for use with multilingual children (Gutierrez-Clellen et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation